Analysis of Optical Properties TiO2, ZnO, TiO2: ZnO Thin Films Deposited On Glass Substrate Using Sol-Gel Spray Coating Method And Application For Degradation Of Dye Liquids. - AMANANTI, WILDA -; amananti, wilda (Faculty of Science and Technology, State Islamic University Walisongo Central Java, 2017)
TiO2, ZnO and TiO2: ZnO Thin film have been deposited on glass substrate by sol-gel method of Spray Coating Technique. TiO2: ZnO and ZnO can form well above the glass substrate. The precursor solution of TiO2 and TiO2: ZnO is deposited using sol-gel method of Spray Coating Technique. Zinc acetate dehydrate (Zn (COOCH3) 2 .2H2O was dissolved into an isopropanol ((CH3) 2CHOH) solvent and then added monoethanolamine (MEA: HOCH2CH2NH2) .The solution was stirred at 70oC until a clear and homogeneous solution was obtained.Titanium Tetraisopropoxide (TTIP) 0 , 73 ml was dissolved into 4.27 ml of isopropanol and 20 ml of ethanol, after which the solution was titrated with 5 ml of ethanol, 3.4 ml acetic acid and 0.26 ml H2O, then stirred on hot plate stirrer at room temperature ( Further, the ZnO, TiO2 and TiO2: ZnO precursor gels were sprayed on a glass substrate that was heated at a temperature of 450 Â° C. The results of the TiO2 thin film bandgap energy measurement were 3.58 eV, ZnO thin films of 3.08 eV, and a thin layer of TiO2: ZnO of 3.06 eV Doped photodegradation dye Direct blue 10 ppm using UV-reactor The highest percentage of degradation is found in TiO2: ZnO thin film